HUBUNGAN ANTARA PERSEPSI PESERTA DIDIK TENTANG KINERJA GURU DENGAN PRESTASI BELAJAR SEJARAH KELAS X SMK NEGERI 7 YOGYAKARTA TAHUN PELAJARAN 2020/2021 - Yumna, Dewi Gina Sari (Universitas PGRI Yogyakarta, 2021)
This study aims to 1) Know the students perceptions about the performance of history teachers at SMK Negeri 7 Yogyakarta. 2) Knowing the history learning achievement of students of class X SMK Negeri 7 Yogyakarta. 3) Knowing the relationship between students' perceptions of teacher performance and history learning achievement of class X SMK Negeri 7 Yogyakarta Academic Year 2020/2021.This research is a quantitative research with a descriptive approach and associative analysis. The population was 353 students and a sample of 184 students was taken. Data collection techniques in this study using documentation and questionnaires that have been tested to determine their validity and reliability. The data analysis technique used descriptive statistics and to test the hypothesis using the correlation analysis product moment. The results of this study indicate 1) Students' Perceptions of Teacher Performance in class X in the medium category with (X= 60.61) 2) History Learning Achievement of Class X in the medium category with (X= 73.76) 3) There is a positive and significant relationship between students perceptions of teacher performance and historical learning achievement in class X (rxy = 0.662). The results of the analysis are positive, meaning that if the variable perceptions of students about teacher performance increase, the achievement of learning history will also increase. In addition, these results are significant so that it can generalize from the existing population.